Human biodistribution and radiation dosimetry for the tau tracer [18F]Florzolotau in healthy subjects - Kun-Ju Lin; Shao-Yi Huang; Kuo-Lun Huang; Chin-Chang Huang; Ing-Tsung Hsiao (SpringerOpen, 2024)
Abstract Background Tau pathology plays a crucial role in neurodegeneration diseases including Alzheimer's disease (AD) and non-AD diseases such as progressive supranuclear palsy. Tau positron emission tomography (PET) is an in-vivo and non-invasive medical imaging technique for detecting and visualizing tau deposition within a human brain. In this work, we aim to investigate the biodistribution of the dosimetry in the whole body and various organs for the [18F]Florzolotau tau-PET tracer. A total of 12 healthy controls (HCs) were enrolled at Chang Gung Memorial Hospital. All subjects were injected with approximately 379.03 ± 7.03 MBq of [18F]Florzolotau intravenously, and a whole-body PET/CT scan was performed for each subject. For image processing, the VOI for each organ was delineated manually by using the PMOD 3.7 software. Then, the time-activity curve of each organ was acquired by optimally fitting an exponential uptake and clearance model using the least squares method implemented in OLINDA/EXM 2.1 software. The absorbed dose for each target organ and the effective dose were finally calculated. Results From the biodistribution results, the elimination of [18F]Florzolotau is observed mainly from the liver to the intestine and partially through the kidneys. The highest organ-absorbed dose occurred in the right colon wall (255.83 μSv/MBq), and then in the small intestine (218.67 μSv/MBq), gallbladder wall (151.42 μSv/MBq), left colon wall (93.31 μSv/MBq), and liver (84.15 μSv/MBq). Based on the ICRP103, the final computed effective dose was 34.9 μSv/MBq with CV of 10.07%. Conclusions The biodistribution study of [18F]Florzolotau demonstrated that the excretion of [18F]Florzolotau are mainly through the hepatobiliary and gastrointestinal pathways. Therefore, a routine injection of 370 MBq or 185 MBq of [18F]Florzolotau leads to an estimated effective dose of 12.92 or 6.46 mSv, and as a result, the radiation exposure to the whole-body and each organ remains within acceptable limits and adheres to established constraints. Trial registration Retrospectively Registered at Clinicaltrials.gov (NCT03625128) on 12 July, 2018, https://clinicaltrials.gov/study/NCT03625128 .